Genetic characterization of non-O157 verocytotoxigenic escherichia coli isolated from raw beef products using multiple-locus variable-number tandem repeat analysis - Franci, Tomas (2011)
Verocytotoxigenic Escherichia coli (VTEC) can produce serious human illness linked to the consumption of contaminated food, mainly of bovine origin. There is growing concern about non-O157 VTEC serotypes, which in some countries cause severe infections in a proportion similar to O157:H7 strains. As several epidemiological studies indicated the important role of meat as the major vehicle in the transmission of this pathogen to human consumers, our aim was to investigate the genetic diversity among non-O157:H7 VTEC isolated from raw beef products. We performed a multiple-locus variable-number tandem repeat (VNTR) analysis (MLVA), and to our knowledge, this is the first time that VTEC serotypes O8:H19, O112:H2, O113:NM, O171:NM, ONT:H7, ONT:H19, and ONT:H21 were typed by this method. MLVA typing grouped the total number of strains from this study (51) into 21 distinct genotypes, and 11 of them were unique. Several MLVA profiles were found in different serotypes, O178:H19 being the most variable. The isolates could be principally discriminated by alleles of three of seven loci studied (CVN001, CVN004, and CVN014), and on the other hand, CVN003 rendered null alleles in all the isolates. As some VNTR markers might be serotype specific, it is possible that the implementation of new VNTR loci will increase intraserotype discrimination.